Effectiveness of situation based learning model on problem solving abilities and mathematical disposition - Sari, Anisa Fatma Kurnia; Arliani, Elly (Jurnal Riset Pendidikan Matematika, 2023)
This study aims to describe the effectiveness of the SBL learning model on the mathematical problem-solving ability and mathematical disposition of grade VIII Junior High School students. The lesson material focuses on the flat-sided shapes of prisms and pyramids. This is an experimental study that uses a one-group pretest-posttest design, and the study population consists of eighth grade students from junior high schools in Klaten, Central Java, which consists of eight classes. The sample was selected using cluster random sampling, and the treatment was administered to class VIII H using the SBL learning model. The study found that the SBL learning model was effective in improving the problem-solving abilities of junior high school students, with an N-gain score of 0.6231. However, it was not effective in improving their mathematical disposition, with an N-gain score of 0.3005. The application of the SBL learning model can be considered as a solution for developing students’ mathematical problem-solving abilities.